INFORMATION AND COMMUNICATION TECHNOLOGIES (ICTS) AS OPPRESSORS OF SOCIAL MOVEMENTS: A POWER PERSPECTIVE - Azer, Evronia; Zheng, Yingqin; Harindranath, G. (AoIR Selected Papers of Internet Research, 2020)
While the literature discusses ICTs as enablers of activism, this paper discusses the manipulation of power through ICTs in activism. Power makes using ICTs in activism dangerous and risky. This paper is a product of 30 semi-structured interviews with Arab Spring grassroots human rights groups that operated before 2015 but no longer do because of oppression and how it affected them physically and psychologically. The paper explains power structures enabled by ICTs inside and outside social movements. It also discusses how the power manifested through ICTs creates much risk of different types for activists: technical, social, psychological and political. First, ICTs created more ways for authoritarian regimes to watch over activists. The asymmetry of visibility (Brighenti, 2010) is one result of the advancements in ICTs that directly affected activists’ mental health by creating anxiety among them, not knowing when and how they are being watched. This asymmetry has also endangered activists’ lives, because if they are unaware of being under surveillance and take no precautionary measures, they are an easy target for state oppression. The two conflicting sides, activists and the state, both make use of ICTs as a space for action turning ICTs into an arena for power struggle. Another side of power that this paper discusses exists within social movements that are claimed to be leaderless. Even though activists do not want to be in an authoritarian system, they create a situation whereby their refusal to decide who is in charge may lead to an implicit power hierarchy.